2012
DOI: 10.1287/orsc.1110.0700
|View full text |Cite
|
Sign up to set email alerts
|

Digital Science and Knowledge Boundaries in Complex Innovation

Abstract: Drug discovery is a complex innovation process in which scientists need to make sense of ambiguous findings and grapple with numerous unpredictable interdependencies over many years of product development. Digitalization has combined with expanding science to address this complexity, creating new ways to measure, analyze, and model chemical compounds, diseases, and human biology. We interviewed 85 scientists and managers working on drug discovery to understand how they deal with complexity. We find a major kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
151
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(157 citation statements)
references
References 29 publications
2
151
0
4
Order By: Relevance
“…Henderson and Clark (1990) found that well-mirrored incumbents making photolithographic equipment lacked the internal capabilities to assimilate-or even perceive the advantages of-architectural innovations. Similarly, in the chemical, steel, and pharmaceutical industries, Collinson and Wilson (2006) and Dougherty and Dunne (2012) found that communication patterns and problem-solving strategies that had evolved under a prior technical architecture, prevented companies from perceiving innovations that cut across organizational boundaries. The consequences can be severe: Brusoni and Prencipe (2011) showed that reliance on the organizational ties developed under a previous technical architecture led to the grounding of two aircraft fleets due to design flaws.…”
Section: The Dynamics Of Mirroringmentioning
confidence: 99%
“…Henderson and Clark (1990) found that well-mirrored incumbents making photolithographic equipment lacked the internal capabilities to assimilate-or even perceive the advantages of-architectural innovations. Similarly, in the chemical, steel, and pharmaceutical industries, Collinson and Wilson (2006) and Dougherty and Dunne (2012) found that communication patterns and problem-solving strategies that had evolved under a prior technical architecture, prevented companies from perceiving innovations that cut across organizational boundaries. The consequences can be severe: Brusoni and Prencipe (2011) showed that reliance on the organizational ties developed under a previous technical architecture led to the grounding of two aircraft fleets due to design flaws.…”
Section: The Dynamics Of Mirroringmentioning
confidence: 99%
“…IT offers a basis to acquire, collect, and internalize data and information, thereby enhancing the analytical capability of an organization and contributing to build organizational knowledge [23]. Especially for complex and technical undertakings, digital platforms serve to understand, synthesize, and apply knowledge in innovations developing [14,53]. Consequently, this research investigates IT knowledge as essential organizational resource to achieve IT-enabled organizational innovativeness, as the strategic relevance of IT knowledge was widely established [6,30,32,48].…”
Section: Organizational Knowledgementioning
confidence: 99%
“…In particular in knowledge-intensive industries, influential IT leadership establishes profound IT capabilities [8] and contributions of IT to firm efficiency and strategic growth [9]. As strategically innovation oriented firms are proven to utilize IS for shifting knowledge in their innovation cycle [14,45], we propose:…”
Section: Figure 1 Research Modelmentioning
confidence: 99%
“…Within such organizations, innovations materialize despite and not because of organizational support. This is because innovation journeys feed upon and generate ambiguity and complexity (Garud, Gehman & Kumaraswamy, 2011b;Dougherty & Dunne, 2012), whereas traditional organizations designed around scientific management principles seek clarity and consistency. This mismatch is a challenge that many organizations confront when it comes to sustaining innovations.…”
Section: Applying the Substance-process Duality To Innovations And Ormentioning
confidence: 99%